Effects of growth promoter and multivitamin-mineral premix supplementation on body weight gain in broiler chickens (Journal of the Bangladesh Agricultural University, 2013)
An experiment was conducted at the Khanpura Poultry Farm, near to the Babugonj campus of Patuakhali Science and Technology University, Patuakhali during the period from August to September, 2011 to evaluate the effect of growth promoter and multivitamin-mineral premix on the body weight gain in broiler chickens. A total of 90 Cobb 500 day-old broiler chickens were randomly divided into three equal groups (n = 30), namely Groups A, B and C. Broiler birds in groups A and B were supplemented with growth promoter and multivitamin-mineral premix, respectively in addition to commercial feed from day 4 till day 25. The dose of both the growth promoter and multivitamin-mineral premix was 2.5 g/kg of feed. Chickens of group C served as control and supplemented with commercial feed only. Body weight was recorded at three times as on day 11, 18 and 25, respectively. The mean body weight was insignificantly (p > 0.05) higher in birds of groups A (992.5±139.6g) and B (978.3±147.0g) than those of group C (926.7±133.2g). The percent increase in body weight gain compare to control was increased in both the supplemented groups (5.8% in group A and 8.8% in group B) though there was no significant difference. Based on the results, it is suggested that supplementation of growth promoter and multivitamin-mineral premix in broilers even after feeding of commercial feed has positive effect on the growth of broilers.DOI: http://dx.doi.org/10.3329/jbau.v10i2.14914 J. Bangladesh Agril. Univ. 10(2): 245-248, 2012